2020
DOI: 10.1182/blood-2020-141505
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Ex Vivo Expanded Healthy Donor-Derived Double Negative T Cells for the Treatment of AML Relapsed after Allogeneic Stem Cell Transplantation: A First in-Human Phase I/IIa Clinical Trial

Abstract: BACKGROUND Relapse after allogeneic hematopoietic stem cell transplantation (allo-HSCT) remains the main cause of treatment failure for patients with acute myeloid leukemia (AML). Conventional treatments such as donor lymphocyte infusions (DLI) or secondary allo-HSCT as a monotherapy or in combination with novel agents or immunotherapy showed limited improvements on long-term survival. Our previous studies have shown that a rare subset of CD4- and CD8- double negative T cells (DNTs) expanded fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…However, we recognize that extrapolating the findings of DNTs to T conv cells should be done with caution. Because DNTs can be expanded ex vivo and have been safely administered to patients with relapsed and refractory AML, 28 there may be an opportunity to combine DNT therapy with venetoclax and azacytidine to further enhance their antileukemic activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, we recognize that extrapolating the findings of DNTs to T conv cells should be done with caution. Because DNTs can be expanded ex vivo and have been safely administered to patients with relapsed and refractory AML, 28 there may be an opportunity to combine DNT therapy with venetoclax and azacytidine to further enhance their antileukemic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the risk of off-tumor toxicities can still persist with incomplete TCR knockout, as 10% of patients treated with allogeneic CAR-T convs knocked out for the endogenous TCR still developed GvHD in the clinic ( 10 ). A phase 1 clinical trial using NT-DNTs shows that none of the 12 AML patients treated with three doses of allogeneic NT-DNTs develop GvHD, grade >2 cytokine release syndrome (CRS), or neurotoxicity ( 25 ). Here, we showed that infusion of CAR19-DNTs without further genetic modification did not cause xenogeneic GvHD or any clinical symptoms of CRS or neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Allogeneic DNTs also fulfill the requirements of an off-the-shelf adoptive cellular therapy, including scalability of expansion, donor-independent anticancer activity, cryopreservability, resistance to HvG rejection, and no observed off-tumor toxicity ( 18 ). A completed phase 1/2a clinical trial using third-party donor-derived genetically nonmodified DNTs to treat patients with relapsed/refractory acute myeloid leukemia (AML) shows that the therapy has a positive safety and efficacy profile ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, none of the patients has developed GVHD or experienced adverse events higher than grade 2 thus far, while all patients experienced grade 1 or 2 cytokine release syndrome and then recovered quickly. Thus, this clinical study showed that allo-DN T cell therapy is safe and tolerable for AML patients, and an expanded patient cohort is urgently required for the next phase of the clinical trial ( 113 , 114 ).…”
Section: Dn T Cells In Tumor Immunotherapymentioning
confidence: 95%